Preparation and Characterization of Aqueous Bifunctional Fe3O4/CdSe/CdS Nanocomposites and Its Application in Immunolabelling of Cancer Cells - Yang, Dongzhi; Sun, Shian; Du, Yan; Zheng, Junnian (Asian Journal of Chemistry, 2014)
A novel method to prepare aqueous magnetic and luminescent Fe3O4/CdSe/CdS nanocomposites was demonstrated. Fe3O4 magnetic nanoparticles were first synthesized by a chemical coprecipitation method with PEG4000 as stabilizer. After being modified by citric acid, the Fe3O4-COOH magnetic nanoparticles were coated with silica shells by Stober method, followed by modification with thiol groups through the sol-gel method. The surface-modified Fe3O4 nanoparticles were lastly linked to CdSe/CdS quantum dots, which were synthesized in aqueous solution with thioglycolic acid as stabilizer, to form Fe3O4/CdSe/CdS bifunctional nanocomposites through coordination. Their optical and structural properties were characterized by photoluminescence, vibrating sample magnetometer and X-ray diffraction studies. It was indicted that the water soluble nanocomposites possess both the magnetic and photoluminescence properties. It was used as fluorescent label in detection of carcinoembryonic antigen, a cancer marker expressed on the surface of HeLa cells. The present study demonstrates the practicability of the prepared nanocomposites as an attractive type of fluorescent labels for biological applications.